Economic analysis and risk assessment of biomass gasification CHP systems of different sizes through Monte Carlo simulation. (November 2021) - Colantoni, Andrea; Villarini, Mauro; Monarca, Danilo; Carlini, Maurizio; Mosconi, Enrico Maria; Bocci, Enrico; Rajabi Hamedani, Sara
Abstract: The deployment of bioenergy has turned into a severe issue associated with energy security and greenhouse gas reduction. The development of technologies in the renewable energy market depends on the profitability of their investment. However, the Net Present Value of new technologies' investment is affected by technical and economic uncertainties. Hence, the probability assessment of a positive Net Present Value and identifying critical economic and technical parameters can inform investors and decision-makers about any investment risks. This study evaluates the overall uncertainty in the Net Present Value of investment in cogeneration plants composed of a gasifier fed with biomass and a bottoming Internal Combustion Engine fed by the gasification product gas. Monte Carlo simulation assesses the probability of a positive Net Present Value for three sizes of cogeneration plants. Regarding sizes, the chance of generating a positive Net Present Value ranges from 66% to 90%, while the larger plants have a higher chance. The sensitivity analysis findings show that above all, biomass cost and then the sale price of electricity and the quantity of gasification product gas are the most dominant parameters. Using an internally produced biomass waste resource and possible achievement of green energy certificates on energy produced would make the initiative successful.